Stakeholder Perspectives on Environmental Accounting Disclosure: A Case Study of North Toraja District Government - Timang, Vica Vanessa Sesaryo (AIBPM Publisher, 2023)
This research uses an ethnographic approach to explore environmental accounting reporting practices in the Local Government of North Toraja Regency. Through participatory observation, in-depth interviews, and document analysis, qualitative data were obtained to understand the dynamics of environmental accounting practices at the local level. The findings show the complexity of environmental accounting reporting practices, which are not only influenced by economic and environmental factors, but also closely related to local cultural preservation needs. Interviews with stakeholders, including government officials, environmentalists, financial officers, and research employees, revealed additional dimensions of environmental accounting practices. The integration of these practices with local cultural preservation highlights the central role of socio-cultural aspects in environment-related decision-making. In addition, the importance of active community involvement and proper budget allocation was highlighted, with adequate financial support considered crucial for the effective implementation of the practice. Interviews with the private sector indicate that environmental accounting practices are considered a strategic tool to support a sustainable corporate image. Corporate social responsibility is not only seen as a regulatory obligation, but also as a positive contribution to the local community and environment. This research makes a significant contribution to the understanding of environmental accounting reporting practices in the Local Government of North Toraja Regency. The findings not only illustrate the complexity of the practice, but also provide an in-depth view of how cultural values, community involvement, prudent budget allocation, and the spirit of innovation become key elements in understanding and improving environmental accounting practices at the local level.